Acupuncture for overactive bladder in adults: Study protocol for a randomized controlled trial - Fengqin Cao; Diyuan Ma; Yueying Chen; Qiongqiong Liu; Ran Pang (Journal of Traditional Chinese Medical Sciences)
Background: Overactive bladder (OAB) is a prevalent condition that substantially degrades patient quality of life. Acupuncture is recognized as an effective therapeutic approach for various urological diseases. However, there is limited evidence validating the effectiveness and safety of acupuncture for OABs. Objective: To assess the therapeutic efficacy of acupuncture for OAB and to investigate the potential mechanisms by analyzing its effects on relevant urinary biomarkers. Methods: This is a randomized, participants and outcome assessors blinded, sham acupuncture controlled trial. A total of 110 patients with OABs will be randomly divided in a 1:1 ratio between the acupuncture and sham acupuncture groups. Participants in the acupuncture group will undergo 30-min authentic acupuncture, while their counterparts in the sham acupuncture group will undergo sham acupuncture needling non-acupoints superficially three times weekly for a duration of 8 weeks. The two co-primary outcomes will be the change in the mean number of micturitions per 24 h from baseline to the end of the 8-week treatment and 20-week follow-up. The secondary outcomes will encompass the change in Overactive Bladder Symptom Score, Overactive Bladder Questionnaire Short Form, and average 24 h values of urgency, daytime micturition, nocturia, and mean volume voided per micturition from baseline to weeks 8 and 20. Urinary nerve growth factor, brain-derived neurotrophic factor, and monocyte chemoattractant protein-1 levels will be measured at baseline and week 8. Adverse events will also be documented. Discussion: The results of this trial will provide evidence for the effectiveness and safety of acupuncture in the management of OAB.